1995
DOI: 10.1007/bf02254183
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D metabolites in childhood nephrotic syndrome

Abstract: We measured serum levels of total and ionised calcium, phosphate, intact parathyroid hormone, 25-hydroxyvitamin D [25(OH)D], 1,25-dihydroxyvitamin D [1,25(OH)2D] and the vitamin D binding protein (DBP) in 14 children with idiopathic nephrotic syndrome and 10 healthy, age-matched controls. In all nephrotics serum DBP levels were below the normal range. Serum 25(OH)D was below 7 ng/ml in 10 of 14 nephrotic children and in the low normal range in the remaining 4 patients. The average serum 1,25(OH)2D levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 21 publications
3
44
0
1
Order By: Relevance
“…The data in the literature on changes in the DBP and total 1,25(OH) 2 D in nephrotic syndrome are equivocal. Some authors report lower concentrations of DBP (2,20,21), and in some studies a correlation between serum albumin and DBP levels was found (12,21). In contrast, other investigators report unchanged levels of DBP in patients with nephrotic syndrome (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data in the literature on changes in the DBP and total 1,25(OH) 2 D in nephrotic syndrome are equivocal. Some authors report lower concentrations of DBP (2,20,21), and in some studies a correlation between serum albumin and DBP levels was found (12,21). In contrast, other investigators report unchanged levels of DBP in patients with nephrotic syndrome (22).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other investigators report unchanged levels of DBP in patients with nephrotic syndrome (22). Likewise, total 1,25(OH) 2 D levels have been found to have decreased (12,21,23,24) or to have been unchanged (22,25) in patients with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This could represent chronic inflammation, an aspect of many comorbid illnesses, which may also associated with decreased UV exposure; however, further adjustment for several documented comorbidities (coronary artery disease, hypertension, chronic obstructive pulmonary disease, cancer, peripheral vascular disease, stroke, congestive heart failure, and liver disease), white blood count, and ferritin did not materially alter the relationship of albumin with vitamin D deficiency. Another such mechanism might be nephrotic syndrome, which is associated with urinary losses of albumin and may also contribute to loss of vitamin D binding protein, the major carrier protein for vitamin D (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…All patients aged more than 18 years, who presented with nephrotic syndrome, were included in the study. Nephrotic syndrome was defined as 24-h urinary protein excretion >3.5 g/1.73m 2 or spot urinary protein creatinine ratio >2.0. Patients with acute sickness, pregnancy, lactation, diabetes mellitus and previously diagnosed patients with hypothyroidism were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Urinary loss of thyroid binding globulin is accompanied with loss of thyroxine (T4) and triiodothyronine (T3). [3][4][5][6] This leads to decrease in serum total thyroxine (TT4) and serum total triiodothyronine (TT4) concentrations and increases the demand on thyroid gland to produce more T4.…”
Section: Introductionmentioning
confidence: 99%